Special issue Cassandra's curse : the law and foreseeable future disasters - Sarat, Austin (Studies in law, politics, and society ;, 2015)
This special issue of Studies in law, politics, and society examines the relationship between law and disasters. The papers come from members of the Collaborative Research Network on the Jurisprudence of Disasters within the Law and Society Association. This network was formed in 2012 at a conference held by the International Institute for the Sociology of Law, titled "Workshop on Disasters and Sociolegal Studies." The volume addresses the 'myths' of contemporary disaster law and policy, such as that of society's "invincibility". The papers examine specific cases such as the Fukushima Nuclear Disaster, bushfire management in Australia and wildfire prevention in the Mediterranean, as well as providing broader analysis and comment on global disaster law and policy.